2011
DOI: 10.1038/nphys1891
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of imprinted antiferromagnetic vortex states in CoO/Fe/Ag(001) discs

Abstract: In magnetic thin films, a magnetic vortex is a state in which the magnetization vector curls around the centre of a confined structure 1. In a thin-film disc, vortex states are characterized by the vortex polarity and the winding number 2,3. In ferromagnetic (FM) discs, these two parameters have been shown to govern many fundamental properties of the vortex, such as its gyroscopic rotation 4 , polarity reversal 5-7 , core motion 8 and vortex-pair excitation 9. In antiferromagnetic (AFM) discs 10 , in contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 23 publications
5
51
0
Order By: Relevance
“…For example, divergent vortices cannot form whenever a ferromagnetic component is present. In contrast, compensated antiferromagnetic materials can form divergent vortices in disks because they do not produce magnetic charges at the disk boundary (Wu et al, 2011). Another example can be found in domainwall dynamics.…”
Section: Magnetic Texturesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, divergent vortices cannot form whenever a ferromagnetic component is present. In contrast, compensated antiferromagnetic materials can form divergent vortices in disks because they do not produce magnetic charges at the disk boundary (Wu et al, 2011). Another example can be found in domainwall dynamics.…”
Section: Magnetic Texturesmentioning
confidence: 99%
“…III.B). Finally, imprinting multidomain states and magnetic textures in antiferromagnets can be achieved by preparing the ferromagnet in specific magnetic configurations, e.g., multidomain (Brück et al, 2005;Roshchin et al, 2005) and vortex (Salazar-Alvarez et al, 2009;Wu et al, 2011) states. Section I.C.4 is devoted to antiferromagnetic textures.…”
Section: Manipulation By Exchange Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…CoO is a compound of very broad interest in particular in the fields of catalysis [12,13], energy storage [14][15][16] and magnetism [17][18][19][20][21][22][23][24], being an antiferromagnetic insulator. Furthermore, CoO films coupled to ferromagnetic substrates (like Fe), show the well-known and technologically important exchange bias effect [25,26], which makes this kind of systems even more appealing.…”
Section: Introductionmentioning
confidence: 99%
“…17 In particular, the CoO/Fe(001) interface has been a workbench for many investigations related to AF/FM systems with reactive interfaces, ranging from the exchange bias mechanism, 14,18 to the influence of structure and stoichiometry on the magnetic properties, 19 to the realization of peculiar magnetic configurations, like vortices. 20 Very recently, we have demonstrated that it is possible to prepare a CoO/Fe(001) interface characterized by the absence of any Fe oxide, 21,22 which is a quite unique feature with respect to the common experimental situations. 10,19,23 This result has been accomplished by exploiting an ultra-thin Co buffer layer with a bct cubic structure.…”
mentioning
confidence: 99%